Experimental Analysis of a Node B Coverage Based on the CPICH and Ec/Io Values - Zamudio-Castro, Iván; Vidal-Beltrán, Sergio; Ponce-Rojas, Jazmín; Sosa-Pedroza, Jorge (Scientific Research Publishing, 2011)
This paper presents experimental results of a coverage analysis in a WCDMA network using the 850 MHz band; an urban electromagnetic propagation environment is considered. Obtained coverage estimation maps are based on Krige statistical method of interpolation. Key performance parameters used in this work are the CPICH and Ec. The results could be used to identify problems and help to optimize cell coverage and capacity in a given service area.
Keywords: WCDMA; Coverage Analysis; CPICH; Ec/Io